The Study of Bogor Botanical Garden Ecotourism Value Chain - Doni Yusri; Arief Daryanto; Hadi K. Purwadaria (Jurnal Manajemen & Agribisnis, 2012)
The objective of this study were : 1) to improve development of Bogor Botanical Garden ecotourism value chain, 2) to recommend strategies of development for Bogor Botanical Garden ecotourism value chain, and 3) to formulate programs that increase value added for Bogor Botanical Garden value chain, especially for involved SME’s. Data collected from survey, in depth interview, and literature was analyzed using descriptive analysis, value chain analysis, SWOT analysis. The results of SWOT analysis indicated that the strength of The Bogor Botanical Garden value chain was the well known Bogor Botanical Garden, the weakness was lack of investment to improve the Bogor Botanical Garden, the opportunity was the support of government, and the threat was the growing of ecotourism competitor. Recommended strategies were : 1) relying on the strenghts of Bogor Botanical Garden as a focal point of the plus ecoedutourism programs, 2) improving quality of human resources at each value chain, 3) increasing investment for the development of value chain, and 4) marketing Bogor Botanical Garden as past of various integrated packages with other tourism objective in Indonesia.Keywords: Bogor Botanical Garden, Ecotourism Value Chain, SWOT Analysis